Effect of energy level of photobiomodulation therapy on bone repair in rats = Efecto del nivel de energía de la terapia de fotobiomodulación sobre la reparación ósea en ratas - Cubas Mogollón, José William
The aim of this experimental study was to determine the effect of photobiomodulation therapy on bone repair in a rat tibia osteotomy model at 15 and 30 days. The sample consisted of 36 male Holtzman rats that were randomized into 6 equal groups. Groups A1 and A2: osteotomy + 1 J laser energy. Groups B1 and B2: osteotomy + 3 J laser energy. Groups C1 and C2 (controls): osteotomy only. The bone repair was analyzed by histological evaluation of osteoblasts and osteocytes both at 15 days (groups A1, B1, and C1) and at 30 days (groups A2, B2, and C2). Within the results, in all groups a greater number of osteoblasts was found at 15 days vs 30 days (p<0.05), and a greater number of osteocytes in B1 and C2 vs B2 and C1, respectively (p<0.05). When evaluating the 3 groups worked up to 15 days, more osteoblasts were found in A1 and C1 vs B1 (p<0.001); and osteocytes predominated in A1 and B1 vs C1 (p<0.001). At 30 days there was a greater quantity of osteoblasts in C2 vs A2 and B2 (p<0.05) and of osteocytes in C2 vs B2 (p<0.05). It is concluded that 1 J photobiomodulation therapy improved bone repair at 15 days; however, this improvement was not observed at 30 days because there were no differences between the irradiated groups and the control.